Perletakan batu asas bangunan tambahan Maktab MARA - Perpustakaan Tun Abdul Razak, Jabatan Arkib Universiti (2016)
Pada 12 September 1966 Timbalan Perdana Menteri Dato Abdul Razak bin Hussien telah menyempurnakan Upacara Perletakan Batu Asas Bangunan Tambahan Maktab MARA di Petaling Jaya Di antara ucapan beliau pada majlis tersebut adalah "The other connection between today's ceremony and a Federal Land Development Scheme is that today I am called upon to lay the foundation stone for a new College for the Bumiputera In Land Development Schemes, I am called upon to plant the first tree, or sow the seeds of the first plant and so it is today in laying the foundation stone for this new MARA College, I feel that I am sowing the seeds of greater Bumiputera participation in the trade, industry, commerce and business of our country"